Bacterial Conjunctivitis in Childhood: Etiology, Clinical Manifestations, Diagnosis, and Management - Leung, Alexander K.C.; Hon, Kam L.; Wong, Alex H.C.; Wong, Andrew S. (Recent Patents on Inflammation & Allergy Drug Discovery, 2018)
Background: Bacterial conjunctivitis is a common reason for children to be seen in pediatric practices. A correct diagnosis is important so that appropriate treatment can be instituted. Objective: To provide an update on the evaluation, diagnosis, and treatment of bacterial conjunctivitis in children. Methods: A PubMed search was completed in Clinical Queries using the key term “bacterial conjunctivitis”. Patents were searched using the key term “bacterial conjunctivitis” from www.freepatentsonline.com and www.google.com/patents. Results: In the neonatal period, bacterial conjunctivitis is rare and the most common cause of organism is Staphylococcus aureus, followed by Chlamydia trachomatis. In infants and older children, bacterial conjunctivitis is most often caused by Haemophilus influenzae, Streptococcus pneumoniae, and Moraxella catarrhalis. Clinically, bacterial conjunctivitis is characterized by a purulent eye discharge, or sticky eyes on awakening, a foreign body sensation and conjunctival injection (pink eye). The diagnosis is made clinically. Cultures are unnecessary. Some authors suggest a watchful observation approach as most cases of bacterial conjunctivitis are self-limited. A Cochrane review suggests the use of antibiotic eye drops is associated with modestly improved rates of clinical and microbiological remission as compared to the use of placebo. Various investigators have also disclosed patents for the treatment of conjunctivitis. Conclusion: The present consensus supports the use of topical antibiotics for bacterial conjunctivitis. Topical antibiotics shorten the course of the disease, reduce discomfort, prevent person-to-person transmission and reduce the rate of reinfection.
Keywords: Haemophilus influenza